Maternal risk factors and neonatal outcomes associated with low birth weight - Shaohua, Yang; Bin, Zheng; Mei, Liu; Jingfei, Zhai; Pingping, Qiao; Yanping, He; Liping, Zhu; Jiexin, Yan; Guoshun, Mao (Frontiers in Genetics, 2022)
Objective: This study aims to evaluate the incidence of low birth weight (LBW) and related maternal risk factors (during pregnancy or childbirth) and neonatal outcomes. Methods: A retrospective cross-sectional study design was used to select 7421 pregnant women who gave birth in our hospital from January 2018 to June 2021. The data were analyzed using STATA 14.1, and the dependent variable (LBW) and risk were analyzed by the chi-square test of independence. The association between factors is used to determine the factors related to LBW through bivariate and multivariate logistic regression. Results: The incidence of LBW in this study was 4.77%. Compared with single pregnant women, the probability of newborn LBW in married pregnant women is 40% lower (AOR=0.60 95%CI: 0.40-0.90, p=0.013). Compared with gestational age less than 37 weeks, the LBW probability of gestational age 37-42 weeks and 42 weeks or older is 85% and 81% lower respectively (AOR=0.15 95% CI: 0.10-0.24, p=0.001; AOR=0.19 95 %CI: 0.09–38, p=0.001), compared with normal pregnant women, the probability of neonatal LBW among pregnant women with hypertension is 94% higher [AOR=1.94 (95% CI: 1.39–2.74, p=0.001). Compared with neonates with normal birth weight, neonates with LBW are at Apgar 1min And Apgar 5min score is lower than 7 (AOR=0.52 95%CI: 0.37-0.73, p=0.001, AOR=0.54 95%CI: 0.38-0.75, p=0.001) higher risk. Conclusion: Women’s marital status (single), gestational age (<37 weeks), and combined hypertension are independently associated with LBW, and the higher risk of Apgar 1min and Apgar 5min scores <7 is an independent result of LBW.